Creativity-culture and tourism-contemporary urban development strategies - Ebru Kerimoglu; Ferhan Gezici (European Regional Science Association (ERSA), 2010)
There was a general shift in the advanced economies from manufacturing to service industries, which emphasized close attention to customers' needs (O'Connor, 2007). This shift has a tremendous impact on the way of life, the use of land, the buildings and neighbourhoods in the city (Modder and Saris, 2005). This 'new economy' was seen to be about innovation, creativity, flexibility, reflexivity, responsiveness - precisely those qualities exemplified in the creative industries. (O'Connor, 2007). In recent decades, creative industries that contribute to a city's social fabric, cultural diversity and enhance quality of life (UNESCO, 2004), as a heterogeneous area of the economy that produces goods and services with creative artistic content for a mass audience has increasingly become a part of cultural and economic policy (Waldner, 2007). Creative industries are increasingly becoming important components of modern post-industrial knowledge-based economies (UNESCO, 2006) and a source for new business, employment, exports and spin-off to other economic sectors (Santacana, 2006). Not only are they thought to account for higher than average growth and job creation, they are also vehicles of cultural identity that play an important role in fostering diversity (UNESCO, 2006). They reinforce a sense of community and shared identity and can promote cultural tourism (UNESCO, 2004). The diversity of cultural amenities affects the quality of the environment and it is a factor in attracting tourists and high-skilled workers (Santacana, 2006). The creative potential of a region is of crucial importance to the competitiveness of new activities and regions (Waldner, 2007). This paper presents an overview of creative industries and creative cities, examining Barcelona and Istanbul. Barcelona experience will take part predominantly and the results that Istanbul can obtain from this experience will be discussed.
Keywords: 330; Creativity; Culture; Creative cities; Barcelona; Istanbul